PREVENTING THE NEGATIVE ASPECTS OF CLIMATE CHANGE IS THE NEED OF THE HOUR - Omonov K. Kh (Journal Park Publishing, 2023)
The article discusses the implementation of measures aimed at preventing damage caused by climate change, the perception of damage caused to nature as a result of anthropogenic impact, the need to prevent maximum heating of the atmospheric air and maintain it in a normal state. not only on the scale of one country, but this is the most important thing that faces the countries of the world. It is argued that this is an important issue. In recent years, in order to prevent damage to the economy as a result of extreme conditions, extreme cold, storms mixed with strong winds and rain, several summits have been held aimed at preventing the negative aspects of climate change, initiated by the UN, state leaders, including Presidents The countries of Central Asia have determined their strategy in this direction in this direction.
Keywords: climate, global warming, anthropogenic impacts, storm, drought, summit, storm, biosphere, degradation, consequences of climate change.